(untitled) (Kriminologie - Das Online-Journal | Criminology - The Online Journal, 2025)
The article introduces a new section in KrimOJ that which will regularly present innovations relating to the bibliographical database “KrimDok” and the services offered by the Criminological Information Service (FID Kriminologie).